Genome-wide association study of a Guinea grass (Megathyrsus maximus) diversity panel reveals the genetic basis of agronomic and nutritional traits - Lopez-Contreras, Lina Maria; Denning-James, Kate E.; Carvajal Tapia, Juliana; Arango, Jacobo; Villegas, Daniel Mauricio; Jauregui, Rosa Noemi; Wenzl, Peter; De Vega, Jose J.; Carvajal Yepes, Monica (BioMed Central, 2025)
Guinea grass ( Megathyrsus maximus ) is a common tropical forage crop valued for its high biomass yields, nutritional quality, and adaptability to diverse abiotic stresses. However, the genetic basis of its key agronomic traits remains poorly understood. In this study, we conducted genome-wide association studies (GWAS) using whole genome sequencing (WGS) data from 124 diverse M. maximus genebank accessions, yielding a high-density single-nucleotide polymorphism (SNP) data set of 1,261,156 SNPs after mapping to a related reference genome. Population structure analysis revealed three major genetic subgroups within the collection. Using three complementary GWAS models (Bayesian-information and Linkage-disequilibrium Iteratively Incorporating Knowledge (BLINK), the Fixed and Random Model Circulating Polynomial Unification (FarmCPU), and the Multiple Loci Mixed Model (MLMM)), we identified 25 significant marker-trait associations (MTAs) spanning three major trait categories: (i) phenological and plant-architecture; (ii) nutritional and digestibility; and (iii) productivity and nitrogen-use traits, evaluated under wet-season, dry-season, and greenhouse conditions. Several MTAs were associated with genes related to plant growth and development, lignin biosynthesis, and nitrogen-cycling (including nitrogen uptake and biological nitrification inhibition). Notably, two SNPs were pleiotropic, with one associated with both nitrogen uptake and shoot biomass production, and another shared between crude protein and in vitro dry matter digestibility. Although a complete reference genome is not yet available for M. maximus, our results provide valuable information for future marker validation and breeding. This study highlights the potential of GWAS as a powerful tool for trait dissection and genetic improvement in tropical forage crops. The research represents a step forward in developing more resilient and productive M. maximus cultivars.